Application of the Total Physical Response (TPR) Approach in Enhancing Writing Skills - Wulan Febriyani; Linda Purwanti; Ria Fitri Mawardiningrum (International Forum of Researchers and Lecturers, 2024)
This research examines the application of the Total Physical Response (TPR) approach in improving writing skills. Through this approach, students are actively involved in physical activities related to the concepts being taught, to strengthen the connection between physical movement and writing skills. This study evaluates the effectiveness of TPR in improving students' writing skills and provides insight into the potential of this approach in language learning contexts.